Resistance of wheat genotypes for C biotype of Schizaphis graminum (Rondani, 1852) (Homoptera, Aphididae) - Tonet, Gabriela Lesche; Silva, Rogério F. Pires da (Pesquisa Agropecuaria Brasileira, 1995)
The resistance for non-preference of C biotype of greenbug, Schizaphis graminum (Rondani, 1852), was studied in a group of 18 wheat (Triticum aestivum L.) genotypes. The trial was carried out in a growth chamber with controlled temperature, relative humidity, and photophase, using a complete randormized design with 15 replications. Genotypes were sown in a circular and aleatoric manner and submitted to a 90-specimen population for 96 hours. The number of greenbugs/plant at a 24-hour interval, the percentage of yellowish leaf area, and the type of spot caused by the greenbug on the plants were the parameters assessed. Results obtained evidenced that non-preference and antibiosis mechanisms were not greater for cultivar BR 36 and for lines PF 86418, PF 86423, PF 86413 and PF 86411.